On the Sources of Labor Productivity Variation in U.S. Manufacturing, 1947-1980 - Bernanke, Ben S. (The Review of Economics and Statistics, 1983)
Because it concentrates on the co-movements of jointly determined endogenous variables, the traditional analysts of labor productivity does not directly address the question of the causes of productivity change.This problem is solved by a modelling approach in which productivity and other choice variables are assumed to respond optimally to five broad classes of exogenous (causal) shocks.Although these shocks are unobservable to the econometrician, maximum likelihood estimates of their relative importance in the determination of productivity change are obtained.